PENGUJIAN BEBERAPA JENIS INSEKTISIDA NABATI TERHADAP KUTU BERAS (Sitophilus oryzae L) - Muhammad Isnaini; Elfira Rosa Pane; Suci Wiridianti (Biota, 2015)
The purpose of this study first to determine whether or not capable of  natural insecticides to kill Sitophilus oryzae L and to determine effective of  natural insecticides to kill Sitophilus oryzae L. This type of research is an experimental research with quantitative descriptive and The data collection techniques used is the observation and documentation. The data analyzed with ANOVA analysis techniques followed by BJND test. Based on the comparison of the calculated F value contained in the ANOVA analysis is greater than the F table , either at the significant level of 5 % and the 1% significance level (79.57 > 2.67 / 4:43). Thus stated that H1 accepted and rejected H0. The results showed that the first, the natural insecticide able to kill Sitophilus oryzae L and mortality rate highest in Cymbopogon citratus treatment that is equal to 13.2 with the total percentage of mortality of 66%, both effective plant-based insecticides to kill Sitophilus oryzae L that leaves just Cymbopogon citratus (66% ) and Morinda citrifolia L (60%).The conclusions obtained from this study: First, some kind of  natural insecticide able to kill Sitophilus oryzae L,  second based on the results of the ANOVA analysis of all types of insecticides to kill Sitophilus oryzae L effectively, but if effectiveness was seen by the number of mortality up to 50 % or more, then just Cymbopogon citratus and Morinda citrifolia L.